Stock Return Determinants In Stock Market Movements - SUHARMADI, Suharmadi; SURIPTO, Suripto (International Journal of Environmental, Sustainability, and Social Science, 2021)
The purpose of this study was to examine the effect of Economic Value Added (EVA), Market Value Added (MVA), Residual Income (RI), Earnings Per Share (EPS) and Operating Cash Flow (OCF) on Stock Returns. Samples used in the study were 22 of LQ-45 index companies listed on the Indonesia Stock Exchange. This study uses multiple linear regression analysis, with partial hypothesis test (t test), simultaneous test (f test), and coefficient of determination (adjusted R). The results of this research indicate that there is an influence from the variable influence of Economic Value Added (EVA), Market Value Added (MVA), Residual Income (RI), Earnings Per Share (EPS) and Operating Cash Flow (OCF) ) towards Stock Return. This is because the company is able to create good performance so that investors can invest in the company.